Fitoremediasi Logam Kromium di Tanah Sawah dengan Rami (Boehmeria nivea) dan Environmental Health Agriculture System (EHAS) - Aji, Alfian Chrisna; Masykuri, Mohammad; Rosariastuti, Retno (Universitas Muhammadiyah Surakarta, 2019)
Chromium metal is one of the heavy metal wastes from various industries and is persistent for the agricultural environment, especially in rice fields. Chromium metal can change biodiversity and ecosystem function in paddy soil. Chromium metal phytoremediation that pollutes paddy soils with hemp (Boehmeria nivea) is important because paddy soils play a role as a living medium for food crops, especially rice (Oryza sativa). One indicator of the success of phytoremediation is the reduction of chromium metal content in the soil, so it requires a policy system to maintain a healthy environmentally friendly agriculture. This study aimed to determine the ability of Boehmeria nivea to reduce levels of chromium metal in the soil and provide policy solutions to keep environmentally healthy agriculture. This study used a complete randomized block design, random sampling of chromium metal data. The results showed the initial concentration of chromium metal in the soil was 2.36 ppm, after treatment with the interaction between Agrobacterium sp. I3 with Boehmeria nivea (P0B1T1) and interaction of organic matter (compost) with Boehmeria nivea (P0B2T1) obtained Cr 1.37 ppm metal content with a decrease of 42.01%. The resulting policy solution is the Environment Health Agriculture System (EHAS). The conclusion of this study was phytoremediation of chromium metal using Boehmeria nivea combined with the Environment Health Agriculture System can create a healthy environmentally friendly agricultural system.